PENGARUH PENERAPAN MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE AND SHARE (SSCS) BERBANTUAN BAHAN AJAR BERMUATAN KARAKTER UNTUK MENINGKATKAN HASIL BELAJAR FISIKA SISWA KELAS XI SMAN 12 PADANG - Fakhrur Rhozy; Yenni Darvina; Murtiani Murtiani (PILLAR OF PHYSICS EDUCATION, 2016)
Students’ achievement on Physic subject has not reached the expectation, yet. It is caused by students’ low-mastery in Physic subject, and the learning material which do not have character values in it. The purpose of this research were to find out the effect of Search, Solve, Create, and Share (SSCS) learning model which had character values in the learning material towards the increasing of students’ achievement of second grade of SMAN 12 Padang. This research used Pre-experimental Designs and One-Group Pretest-postest. The instruments of this research were writing test that was used in pre-test and post-test for testing the knowledge competence, observation sheet for testing the behavior competence, and rubric score for testing skill competence. Linear regression and product moment correlation were used to analyze the data with at the level of significance 0.05. The results revealed that the application of SSCS which had character values in the learning material had positive effect towards students’ achievement in learning Physic for students at the second grade of SMAN 12 Padang for these three competences at the level of significance 0.05